Age-related differences in hamstring flexibility in prepubertal soccer players: An exploratory cross-sectional study - Abate Daga, F.; Panzolini, M.; Allois, R.; Baseggio, L.; Agostino, S. (Frontiers in Psychology, 2021)
This study aimed to investigate the hamstring flexibility rate among prepubertal soccer players from U8 to U12 and the role of age and soccer years of practice on the course of hamstring flexibility. Six hundred eleven young Italian soccer players from a local soccer school in Turin were recruited for this research and assigned to each group according to their chronological age (U8 = 124 players; U9 = 130 players; U10 = 151 players; U11 = 89 players; and U12 = 120 players). Hamstring flexibility was measured using the Sit and Reach Test (SAR), while data analysis was run using a one-way analysis of variance (one-way ANOVA). Furthermore, Tuckey`s post hoc was used to determine differences among the classes of age. Finally, a bivariate ordinal regression analysis was used to evaluate a potential association between age categories and hamstrings flexibility. In addition, multivariable ordinal regression was used to analyze this relationship adjusted for the Body Mass Index (BMI). The one-way ANOVA showed significant differences in flexibility among groups (F = 32.76, P < 0.0001). Tuckey`s post hoc identified significant differences between U8 and U10 (p < 0.01; -2,39 cm of hamstring stretching), U8 and U11 (p < 0.05; -2.19 cm), U8 and U12 (p < 0.0001; -5.90), U9 and U12 (p < 0.0001; -4.98 cm), U10 and U12 (p < 0.0001; -3.5 cm), U11 and U12 (p < 0,001; -3.70 cm). In the bivariate ordinal regression analysis, there was a negative association between the age categories and hamstrings flexibility (R2 = 0.137; p < 0.0001). The association persisted in multivariable ordinal regression analysis adjusted for BMI (R2 = 0.138; p < 0.0001). This study underlines changes in hamstring flexibility across different age groups of prepubertal soccer players. The older and more experienced in soccer are less flexible than the younger, considering the hamstring muscles. Thus, appropriate stretching protocols should be included in prepubertal soccer training to avoid the risk of lead players to excess hamstring tightness.